Leadership by Nurse Managers and its Impact on Humanization. A Descriptive Analysis based on the Perception of Care Nurses - Cortés Borra, Alberto; Jaén Ferrer, Pedro; Gea Caballero, Vicente; Martín García , Sandra; Martínez Estalella, Gemma; Martínez Riera, José Ramón (Investigación y Educación en Enfermería, 2025)
Objective. The objective was to analyze the relationship among sociodemographic factors, management variables, and the perception of care humanization by nursing staff. Methods. A descriptive and observational study was conducted with a sample of 659 nurses working in Spain. A descriptive analysis of the sociodemographic and management variables was performed. Subsequently, a Latent Class Analysis (LCA) was applied to classify participants according to their scores on the HUMAS scale, which measures their perception of their own humanization and that of their manager. Finally, multinomial and logistic regression models were proposed to identify the determinant factors for belonging to these classes and for the opinion on the center of the healthcare system. Results. The sample was composed mostly of women (78.9%) with professional experience and job stability averaging 24.17±10.49 years (Min=1, Max=45). Notable dissatisfaction (58.3%) and distrust (57.9% between little and none) towards managers were detected. The LCA identified four nurse profiles based on their perception of humanization: a class with a high valuation of their own humanization and management (Class 2: c2), one with a low valuation in both (Class 3: c3), one with a high personal valuation but low towards management (Class 4: c4), and an intermediate class (Class 1: c1). The most valued traits in a manager were respect, communication, and transparency. Conclusion. A significant gap exists between nurses’ self-perception of humanization, which is generally high, and their perception of their managers, which is predominantly low. This dissonance, combined with dissatisfaction with leadership, underscores the need to develop management styles that promote communication, respect, and transparency to improve the work environment and the quality of patient care.